(untitled) (Proceedings of the Global Public Health Conference, 2018)
In Sri Lanka, the main occupation of the alcohol users was students according to the International Standard Classification of Occupation. Attractiveness of the image of alcohol is one of the key determinants and this image develops through peer norms. Aim of the study was to assess the effectiveness of a health promotion intervention in changing the attractive image of alcohol among students. A quasi experimental study was conducted among students from grade 8 to 11 from two schools in Anuradhapura and Polonnaruwa districts in Sri Lanka as the intervention and control group respectively. Intervention was delivered through a group of voluntary students from grade 11 with training to challenge peer norms. Data were collected using self-administered questionnaires and the chi square test was performed by SPSS. Acceptance on 7 out of 10 norms towards alcohol were significantly reduced in the intervention group with a p value < 0.05 (95 CI level) by comparing post evaluation results in the intervention group with the post evaluation results in the control group according to the chi square test. A health promotion intervention consists of a trained student group is effective in challenging peer norms for reducing the attractive image of alcohol among students.